Learning progress map (MPA) and route of learning (RL) in Peru - 2013 - LaTorre A., Marino (2013)
This article discusses the Learning Progress Maps (LPM) and Learning Paths, (LP) implemented both by the Ministry of Education of Peru in 2013. Both instruments are designed to strengthen student learning process, to provide indicators to students learning quality therefore at the end of the cycles identified and provide guidance to teachers. We present the theoretical basis of the LPM and a critical analysis of both instruments are done, its origin, its validity and possible readings that can be made of it, depending on the paradigm used by the teacher. At the end it is synthetically exposed the Socio-Cognitive humanist Paradigm as a pedagogical model suitable for the proper use of the instruments studied.